Las teorías democráticas de la autodeterminación y secesión - Ignacio María Beobide Ezpeleta (Estudios de Deusto, 2012)
This paper analyses the democratic theories of self-determination and secession. The first section summarises the most relevant versions of these theories proposed by several authors to identify (a) the common element: the individual consent as the basis of «moral right» to self-determination and secession, and (b) the conditions, notably different, that each author contemplates for the application of this right. The second section undertakes a critical review of these theories. Finally, the conclusions highlight the weaknesses of these theories from the theoretical and methodological viewpoint.